Droplet microfluidics for single cell analysis. - Wang, Ruiping. (2012)
Microfluidic or Lab-on-a-chip devices manipulate small amount of fluids in microscale that are typically on the order of 10 to 100 µm. Such devices or systems have been of great interest as an ideal platform for miniaturized chemical reactions, chemical and biological synthesis, drug diagnosis, cell analysis and so on. The end application functionalities are mainly realized through a combination of geometry structures and chip materials used during fabrication.